2019
DOI: 10.3390/horticulturae5040077
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and Nitrogen Dynamics Affected by Drip Irrigation Methods and Fertilization Practices in a Pomegranate Orchard

Abstract: Knowledge of carbon (C) and nitrogen (N) dynamics under different irrigation practices in pomegranate orchards is novel and essential to develop sustainable production systems. The aim of this research was to determine the effect of high-frequency drip irrigation and different rates of N fertilizer on C and N distribution in the soil and N uptake by pomegranate fruit and leaves. The main treatments were surface drip irrigation (DI) and subsurface drip irrigation (SDI), and the sub-treatments used were three in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 33 publications
(44 reference statements)
2
11
0
Order By: Relevance
“…The field treatments included two main irrigation treatments as surface drip irrigation (DI) and subsurface drip irrigation (SDI) and three N application rates as sub-treatments. The findings on treatment effects on yield, N requirement, and weed as well as C and N dynamics from this field research are reported in Ayars et al [17] and Tirado-Corbalá et al [18], respectively. Conclusions included that although yields were not significantly different between the two irrigation systems, SDI used less water with much lower weed pressure than DI.…”
Section: Introductionsupporting
confidence: 63%
See 4 more Smart Citations
“…The field treatments included two main irrigation treatments as surface drip irrigation (DI) and subsurface drip irrigation (SDI) and three N application rates as sub-treatments. The findings on treatment effects on yield, N requirement, and weed as well as C and N dynamics from this field research are reported in Ayars et al [17] and Tirado-Corbalá et al [18], respectively. Conclusions included that although yields were not significantly different between the two irrigation systems, SDI used less water with much lower weed pressure than DI.…”
Section: Introductionsupporting
confidence: 63%
“…Overall, the lower soil N 2 O concentration in SDI plots than that from DI may also be due to more efficient plant uptake. Tirado-Corbalá et al [18] showed that total N uptake in fruits were significantly higher in SDI plots than that from DI at least for two out of three years. 2013 data (not shown) were similar to those collected in 2012 in distribution patterns except that the N3 treatment plots showed either lower or similar N 2 O concentrations as the N2 treatment plots that were consistent with the emission data.…”
Section: B N 2 O Production In Soil and Correlation With Emission Fluxmentioning
confidence: 95%
See 3 more Smart Citations